2020
DOI: 10.1111/bph.15151
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis (ALS), cancer, autoimmunity and metabolic disorders: An unsolved tantalizing challenge

Abstract: Amyotrophic lateral sclerosis (ALS) commonly referred to as motor neurone disease, is a neurodegenerative disease of unknown pathogenesis that progresses rapidly and has attracted an increased amount of scholarly interest in recent years. The current conception of amyotrophic lateral sclerosis has transitioned into a more complex theory in which individual genetic risk, ageing and environmental factors interact, leading to disease onset in subjects in whom the sum of these factors reach a determined threshold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…These authors described ALS as a complex disease caused by individual genetic risk, ageing and the influence of environmental factors, which interact to determine the threshold for the onset, progression and prognosis of the disease. They discuss the relevance, for the disease, of those environmental conditions that could be modified and review the evidence for cancer, autoimmunity and metabolic disorders, as important conditions leading to ALS (Riancho et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…These authors described ALS as a complex disease caused by individual genetic risk, ageing and the influence of environmental factors, which interact to determine the threshold for the onset, progression and prognosis of the disease. They discuss the relevance, for the disease, of those environmental conditions that could be modified and review the evidence for cancer, autoimmunity and metabolic disorders, as important conditions leading to ALS (Riancho et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…The ALS pathway, which is a progressive and lethal motor disorder, includes in its gene list TP53, several members of the caspase family pathway, TNF and MAP kinases; all of these genes are widely documented as important agents in many cancer phenotypes [ 91 94 ]. Furthermore, a 2016 preclinical study showed how the C9orf72 knockout, the most common cause of ALS, caused an unexpected increase in tumours in mice [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the study was that ALS death rather than incidence was used in CPS-II Nutrition (the Cancer Prevention Study II-Nutrition Cohort), MEC (the Multiethnic Cohort Study), and NIH-AARP (the National Institutes of Health-Association of American Retired Persons Diet and Health Study). However, due to the rapidly progressive nature of ALS (median survival 1 4 1.5-3 years), the authors assumed ALS death to be a reasonable proxy for incidence.…”
Section: Urates and Purinesmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is an incurable chronic progressive neurodegenerative disease with the progressive degeneration of motor neurons in the motor cortex and lower motor neurons in the spinal cord and the brain stem [1]. As a rule, patients die from respiratory failure 3-5 years after onset of the disease.…”
Section: Introductionmentioning
confidence: 99%